A Selective-Awakening MAC Protocol for Energy-Efficient Data Forwarding in Linear Sensor Networks. (10th May 2018) - Villordo-Jimenez, Iclia; Torres-Cruz, Noé; Carvalho, Marcelo M.; Menchaca-Mendez, Rolando; Rivero-Angeles, Mario E.; Menchaca-Mendez, Ricardo
Abstract : We introduce the Selective-Awakening MAC (SA-MAC) protocol which is a synchronized duty-cycled protocol with pipelined scheduling for Linear Sensor Networks (LSNs). In the proposed protocol, nodes selectively awake depending on node density and traffic load conditions and on the state of the buffers of the receiving nodes. In order to characterize the performance of the proposed protocol, we present a Discrete-Time Markov Chain-based analysis that is validated through extensive discrete-event simulations. Our results show that SA-MAC significantly outperforms previous proposals in terms of energy consumption, throughput, and packet loss probability. This is particularly true under high node density and high traffic load conditions, which are expected to be common scenarios in the context of IoT applications. We also present an analysis by grade (i.e., the number of hops to the sink, which is located at one end of the LSN) that reveals that LSNs exhibit heterogeneous performance depending on the nodes' grade. Such results can be used as a design guideline for future LSN implementations.